Monitoring egg fertility, embryonic morbidity, and mortality in an oviparous elasmobranch using ultrasonography - Adams, Lance; Wyffels, Jennifer T.; Goodwin, Brittney; Munson, Rachel; LeBorgne, Louise; Feldheim, Kevin A.; Lyons, Kady (Frontiers in Veterinary Science, 2024)
Ultrasonography is widely used to monitor pregnancy in viviparous species, but it is underutilized as a tool to characterize embryonic development in oviparous species. Currently, a multi-institutional effort is underway to re-wild the endangered zebra shark (Stegostoma tigrinum) to locations where this species was previously extirpated, by leveraging the reproductive efforts of aquarium sharks as a source of brood stock. Zebra sharks are oviparous and fecund, but a large percentage of their yolked eggs do not result in hatchlings. Therefore, ultrasonography represents a potential tool for distinguishing fertile eggs with developing embryos from degrading eggs, and to diagnose changes in early embryonic development predictive of poor outcomes. The objectives of the current study were to use ultrasonography to assess egg fertility, monitor early embryonic development, and identify morphological indicators that may be predictive of early embryonic mortality. Freshly laid eggs from four female zebra sharks were collected and inventoried daily at Aquarium of the Pacific. Eggs were incubated undisturbed for two to four weeks and subsequently examined weekly via ultrasound to assess fertility and monitor embryo development. Among 120 fertile eggs, embryos were identified as early as 8 days post-oviposition, with average (± SD) time to first observation at 30 ± 7 days. Morphological and behavioral abnormalities were observed for most embryos (n = 84, 70%) as early as 16 days and up to 95 days post-oviposition. Common abnormalities included: bent or curled tails, vesicle(s) at the base of the yolk stalk, and slow or weak movement. Only one embryo survived to hatch during the study and was genetically-confirmed parthenogenetic, suggesting hatching success for parthenotes is low (< 1%). Ultrasonography was demonstrated to be an effective and non-invasive method to determine egg fertility, identify embryos with developmental abnormalities, and monitor embryo growth.